PENGARUH PENDIDIKAN TEMAN SEBAYA (PEER EDUCATION) TERHADAP PERILAKU REMAJA PUTRI YANG MENDERITA ANEMIA DI MADRASAH STANAWIYAH ISLAMIYAH JL.SULUH 71 KOTA MEDAN TAHUN 2018 - Surjantini1, Raden Roro Siti Hatati; Saragih2, Hanna Sriyanti (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2018)
Young women are one group that is prone to anemia. Therefore, the target of nutritional anemia preventionprograms has been developed to reach junior high school, high school and equivalent girls, and womenoutside of school as a strategic effort in an effort to break the cycle of nutrition problems. Even so, theprevalence of anemia among young women was still high. Data from the Ministry of Health in 2005 showed26.50% of anemia in young women and 26.9% in fertiled age women. This indicated that anemia was still bea health problem in Indonesia. This type of research is a quasi-experimental one-group pre-test post-testdesign to determine the influence of Peer Education on the behavior of young women who suffer fromanemia in Madrasah Stanawiyah Islamiyah on Jl. Suluh 71 Medan City in 2018. Research instruments usinga questionnaire. The sample chosen in this study was the student of Madrasah Tsanawiyah Islamiyah Jl.Suluh 71 Kota Medan. The statistical test used was the t-test (independent-t test) to test for differences in theaverage Hb level of the study start and increase in Hb levels after administration in both groups. Based onthe results obtained, it can be concluded that there was an influence of peer education (Peer Education) onthe behavior of young women who suffer from anemia in Madrasah Stanawiyah Islamiyah Jl.Suluh 71 KotaMedan Kota in 2018. The average Hb level of subjects increased by 2, 13 after being given an intervention.The average score of subject behavior assessment increased by 34.33 after being given intervention.Expected for students in Madrasah Stanawiyah Islamiyah Jl.Suluh 71 Kota Medan Kota in 2018 in order toget used to eat foods that contain lots of iron which serves to increase hemoglobin levels in the blood thusinhibiting anemia